SISTEM INFOMASI SELEKSI BERKAS LAMARAN CALON GURU SECARA ONLINE PADA SMA LTI INDO GLOBAL MANDIRI PALEMBANG - Yoga Pradifta; Terttia avini; Suryati Suryati (UNIVERSITAS INDO GLOBAL MANDIRI)
SMA LTI Indo Global Mandiri Palembang is one of the private high school in the city of Palembang and not optimally in memenuihi information needs and service selection application file prospective teachers, as an example of selection procedures for application files prospective teachers in SMA LTI IGM Palembang still use process manual, namely in terms of the proposed selection file such applications are not integrated so if there are teachers out of SMA LTI IGM Palembang HRD will find the data the teacher that will take a long time because the data has not been well integrated teacher. and in terms of valuation results of the interview prospective teachers so that in making decisions based on an assessment of the interview test requires considerable time. So I will make the selection of an information system application file online teacher candidates at SMA LTI Indo Global Mandiri Palembang. Researcher using a methodology WDLC (Web Development Life Cycle) and tools UML (Unified Modeling Language) with the aid of use case diagrams, activity diagrams, sequence diagrams and classdiagram. This system can provide information on jobs available, the acceptance criteria, the status of the application is submitted, and a few other things. With this system is expected to facilitate both applicants / prospective teachers as well as the human resources department to manage the process of selection of information system application file online prospective teachers in SMA LTI Indo Global Mandiri Palembang